2006
DOI: 10.1097/01.rct.0000228153.81151.ea
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Appearance of the Lapra-Ty® and Weck Hem-O-Lok Clips in Patients Who Recently Underwent Laparoscopic Urologic Surgery

Abstract: The nonmetal suture securing Lapra-Ty clip (LTC) and vessel ligating Weck hem-o-lock clip (WKHL) are useful tools for the laparoscopic surgeon. We report the postoperative computed tomography (CT) scan appearance of these clips. The CT imaging of patients who underwent urologic surgery demonstrate the WKHL and LTC to be radiopaque. Urologists and radiologists should be aware of the radiographic appearance of the LTC and WKHL given the ease with which they could be confused with urinary lithiasis when applied n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Differences between the radiographic methods used at each institution might have caused the discrepancies between the findings of previous reports. 5 In this study, we found that Hem-o-lok clips were radiopaque on CT scans of patients who had undergone LRN or LRU.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Differences between the radiographic methods used at each institution might have caused the discrepancies between the findings of previous reports. 5 In this study, we found that Hem-o-lok clips were radiopaque on CT scans of patients who had undergone LRN or LRU.…”
Section: Discussionmentioning
confidence: 61%
“…2,5,6 These reports could lead to problems when radiopaque objects, such as Hem-o-lok clips, stones, or foreign bodies, are recognized near to the renal hilum on postoperative CT scans of patients who have undergone LRN or LRU. In particular, when a patient suffers postoperative flank or abdominal pain, radiopaque objects detected on postoperative CT scans might be thought to be foreign bodies related to surgery, such as part of a drainage tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another controversial issue is the detection of Hem-o-lok clips that have migrated into the collecting system. Variable reports about their CT-visibility exist [18,19]. Matsushita et al have shown that the density of hem-o-lok clip was 223 HU, consistent with its ex-vivo CT-based attenuation measurement [20].…”
Section: Discussionmentioning
confidence: 67%